Families' roles in children's literacy in the UK throughout the 20th century. (December 2017) - Nutbrown, Cathy; Clough, Peter; Levy, Rachael; Little, Sabine; Bishop, Julia; Lamb, Terry; Yamada-Rice, Dylan
This paper explores the changing roles of families in children's developing literacy in the UK in the last century. It discusses how, during this time, understandings of reading and writing have evolved into the more nuanced notion of literacy. Further, in acknowledging changes in written communication practices, and shifting attitudes to reading and writing, the paper sketches out how families have always played some part in the literacy of younger generations; though reading was frequently integral to the lives of many families throughout the past century, we consider in particular the more recent enhancement of children's literacy through targeted family programmes. The paper considers policy implications for promoting young children's literacy through work with families.